Teachers' Perception and Attitude towards Gifted Students Focusing on Their Giftedness Characteristics in Primary Schools in Riyadh: Kingdom of Saudi Arabia - Almatroodi, Azizh Abdullah (Journal of Educational and Psychological Sciences, 2023)
Abstract: Gifted students are those who stand out among their peers who are the same age or grade level in terms of their remarkable intellectual or creative ability. This study aimed at investigates teachers' perceptions and attitudes toward gifted students with a focus on giftedness characteristics in mainstream primary schools in Riyadh, Saudi Arabia. Based on the theories of scholars in previous studies, the methodology of descriptive analysis of data, and direct interviews with teachers, the researcher found that Teachers typically had a good understanding of these characteristics. Furthermore, the researcher found that teachers have positive attitudes towards gifted students. The study highlights the urgent need for teacher training programs in the field of gifted education in The Kingdom of Saudi Arabia.
Keywords: Teachers' perception; gifted students; gifted characteristics; Kingdom of Saudi Arabia